Tendência temporal da prevalência de sobrepeso e obesidade em adolescentes escolares: Uruguaiana/RS 2011 a 2018 - Dias, Saulo Menna Barreto (2019)
Evidence from international studies suggest an increase in overweight and obesity in the last decades in children and adolescent population. However, such information is still scarce in the Brazilian population when it comes to temporal trend studies. In this study, we analyzed the temporal trends in the prevalence of overweight and obesity among students aged 10 to 17 enrolled in the public-school system of the city of Uruguaiana/RS between the years 2011 and 2018. This is a cross-sectional study of epidemiological school-based survey type. A total of 616 students in 2011 (database) and 285 students in 2018 took part of the study, enrolled in five schools from the public-school system. To measure overweight and obesity in this population, we used as anthropometric indicators of overweight and obesity the body mass index, waist circumference, and the sum of triceps and subscapular skinfolds. For the analysis of the data, descriptive statistics was used, and to test the possible differences between the data from 2011 and 2018, the chi-square test for heterogeneity and the Student t-test for independent samples were used. A significance level of 5% was adopted. In general, the results indicated a stabilization in the prevalence of overweight and obesity in the population studied in this period. The results of the analysis of the anthropometric indicators of overweight and obesity used showed that both the mean values and the proportions of compliance with the recommendations to the cutoff points found in 2018 did not present statistically significant changes (P>0.05) for body mass index and for the sum of the skinfolds when compared to the results from 2011. Waist circumference, on the other hand, presented a statistically significant increase (P<0.05) of about two centimeters in the mean value and an increase, with no statistical significance, of about five percentage points in the occurrence of adolescents with values considered increased. It was concluded that, despite the stabilization of indicators of overweight and obesity, these indicators have stabilized at high levels, as also seen in other national studies. We emphasize the importance of a greater number of studies on the subject and a greater monitoring of these variables so that actions of treatment and prevention of overweight and obesity are developed for this population.